Implementasi Web Crawling untuk Pencarian Harga Sparepart Pada PT Asuransi Sinar Mas - deddy deddy (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
The availability of vehicle spare part information is one of the main needs in the business processes run by an insurance company. One insurance company that requires the availability of this information is PT. Sinar Mas Insurance. Required spare part information is obtained from the website available on the internet. However, due to the large amount of vehicle spare parts information needed and due to limited time available a program called web crawler is needed. A web crawler is a program that crawls the entire URL of a website, tracks it one by one, then stores all the information contained in that website. Web crawlers in this study use the Scrapy framework with the Python programming language. The website to be crawled in this study is the website Suzuki.co.id/eparts which is a website that contains data and prices for official spare parts specifically for Suzuki cars. This study aims to produce a web crawling application that will be used in finding Suzuki Suzuki auto parts price data automatically.